Efektivitas Metode Jigsaw dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Kelas X SMA PU Al-Bayan Cendekia Cianjur: Pendekatan Kuantitatif - Yuliawanti, Hani; Hoerotunnisa; Hakiki, Kiki Miftahul; Putra, Moch. Ardia; Kariadinata, Rahayu; Miftahul Hakiki, Kiki (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
The Islamic Religious Education (PAI) learning process on the topics of Hajj, Zakat, and Waqf in grade X at SMA PU Al-Bayan Cendekia Cianjur faces challenges due to low student achievement caused by conventional teaching methods that lack active student engagement. This study aims to examine the effectiveness of the Jigsaw method in improving students’ PAI scores using a quantitative quasi-experimental design. The sample consisted of two classes: an experimental group taught using the Jigsaw method and a control group using conventional methods. Data were analyzed using t-tests and n-gain tests to measure significant improvement in scores. The results indicate that the Jigsaw method significantly improves students’ scores on Hajj, Zakat, and Waqf materials, with average n-gain scores in the moderate to high category. This method also enhances student motivation and engagement in learning.